Diversifikasi pengolahan singkong untuk peningkatan kesejahteraan masyarakat - Khoirin Maghfiroh; R.R. Sri Karuniari Nuswardhani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
The community partnership program (PKM) in the cassava processing effort without producing waste was carried out together with PKK ladies groups namely PKK RT.4 RW 1 Loring Sukopuro Jabung District Malang Regency. The lack of technological knowledge causes the processing of cassava is not optimal. Cassava processing still uses simple technology. Most cassava is sold in raw form and some is sold in processed chips, besides that there are no handlers related to waste produced from cassava preparations. But on the other hand, abundant cassava production. This program aims to form an independent business group in the development of processed cassava to produce nutritious products without producing waste. The method of approach used in PKM is the Participatory Rural Appraisal (PRA) approach, which involves partner groups in activities. As for the implementation of this PKM activities include: counseling, training, hands-on practice, and assistance. The results of this program are increasing partners 'knowledge in processing cassava into nutritional products based on waste utilization, knowledge of partners' skills in processing cassava into nutritional products based on waste utilization, partners are able to utilize appropriate technology transfer, and improving management and marketing capabilities.